PROFIL GURU PROFESIONAL DALAM BUKU KINERJA DAN PROFESIONALISME GURU KARYA DONNI JUNI PRIANSA - Nurudin Nurudin; Hifza Hifza; Deni Irawan (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Teachers play a very important role in education. The vital role of teachers becomes even more significant when education is understood as a formal institution, such as the school system. Teachers must be able to transform their students into better, more cultured individuals who are capable of building a modern nation, as described in Donni Juni Priansa's book on teacher performance and professionalism. This researcher uses a qualitative approach, as it emphasises the collection of qualitative data (not in the form of numbers). The type of research used in this study is a literature review (Library Research). A literature review is an analysis conducted to solve a problem that is essentially based on a critical and in-depth examination of relevant library materials. The results of the study show that teachers with academic qualifications of a bachelor's degree in education tend to be more experienced in their profession as educators, as evidenced by recognition from the relevant agencies through certificates of expertise in their profession. Their performance is excellent and they have professional competence in carrying out their duties as educators, such as in creating and archiving learning administration, carrying out teaching and learning activities, both inside and outside the classroom, such as extracurricular learning, and several other teacher performances related to learning at school. Teachers' profiles and performance have a positive role in motivating students to study religious education and develop character-building behaviour, as a reflection of someone who obediently follows religious teachings. The figure of a teacher in everyday school life can bring about a significant change in the thoughts and behaviour of students